The Influence of Recruitment, Work Quality, and Rewards on Improving Employee Performance at PT. Cipta Karya Aceh Bireuen - Zulfahmi, Zulfahmi; Malik, Imam; Abqa, Rizkan (Aceh Cooperative Care, 2025)
This study analyzes the influence of recruitment factors, work quality and rewards on improving employee performance. The study was conducted on 75 employees of PT. Cipta Karya Aceh in Bireuen, a construction company engaged in infrastructure development and large-scale commercial projects. An associative quantitative approach was used with an analysis tool in the form of a path model. The results of the study indicate that 1) There is a causal relationship between recruitment variables, work quality and rewards with a moderate category. 2) There is a direct and indirect influence of each suspected factor, namely recruitment has an influence of 32.74% on employee performance. While work quality is 40.22% and the reward factor is very significant at 48.89%. 3) Simultaneously, the contribution of recruitment factors, work quality and rewards is 69.1% to employee performance.